In vitro activity of riparin III in combination with antimicrobials against multidrug-resistant clinical isolates of Staphylococcus aureus and Acinetobacter baumannii - Jorge Belém Oliveira-Júnior; Fernanda Cristina Gomes de Lima; Elza Ferreira Firmo; Daivyane Aline Mota da Rocha; Jana Messias Sandes; Stanley Juan Chavez Gutierrez; Celso Amorim Camara; José Maria Barbosa-Filho; Luiz Carlos Alves; Fábio André Brayner (Elsevier, 2023)
S. aureus and A. baumannii are among the main bacterial species responsible for several infections worldwide due to the different resistance and virulence mechanisms, which can interfere with treatment. The use of antimicrobial combination is one of the therapeutic options; however, they may exhibit potential for nephrotoxicity and hepatotoxicity. Therefore, the use of natural compounds and antimicrobial combinations has been studied, considering the effectiveness of antimicrobial activity, and reduction of toxic effects. The aim of this study was to analyze the synergistic effect between riparin III and antimicrobials against S. aureus and A. baumannii, as well as possible in vitro ultrastructural changes induced for the synergistic combination. Riparin III and antimicrobial (ciprofloxacin, oxacillin, meropenem and colistin) against multidrug resistant (MDR) clinical isolates and MIC determination using microbroth dilution assay was performed. The checkerboard method and the Fractional Inhibitory Concentration Index (FICI) were used to determine the type of interaction between the different antibiotics and riparin III, and the time-kill assays confirmed the results. Through Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) possible morphological changes in bacterial cells can be observed. S. aureus exhibited resistance to oxacillin, ciprofloxacin, and A. baumannii were both described as resistant to meropenem and isolate 54 was resistant to colistin. FICI for A. baumannii indicated synergism between riparin III and colistin, and MIC reversal revealed a maximal-fold significant reduction in MIC colistin in synergistic combinations. Checkerboard and time-kill demonstrated a potential for synergy in this combination against A. baumannii and showed bactericidal activity. Several ultrastructural changes in A. baumannii treated with the synergistic mixture were visualized for SEM and TEM, such as reduction in the cell number, rough appearance, in addition to indefinite morphologies and total defragmentation of the bacterial cell wall. Therefore, riparin III and colistin combination showed synergism against MDR A. baumannii and decrease in the MIC of colistin, as well as several ultrastructural changes in bacterial cells.